Malignant lesions in the anterior maxilla. Issue 7 (July 2020) - MacDonald, D.; Martin, M.; Nguyen, C.
Abstract : The anterior alveolar ridge of the maxilla is a frequent site for pathology, most of it involving underlying bone and readily observable radiologically. Although much of this disease presents as well-defined unilocular radiolucencies arising adjacent to the apices of non-vital anterior teeth, thus being periapical radiolucencies of inflammatory origin (PRIO), a minority reflects more serious disease such as neoplasia. The most serious of the latter are malignancies, most frequently squamous cell carcinomas (SCCs). Although the majority of SCCs arise from the oral or nasal mucosa and secondarily invade the underlying bone, a proportion arise from epithelial remnants of odontogenesis within the alveolus. These need to be readily distinguished from other more common benign lesions, and also non-Hodgkin lymphomas (NHL). The latter has been reported arising with the alveolus in addition to their more usual nodal and extranodal sites. The rarer malignancies that could arise within the anterior maxilla are addressed in the text with particular reference to the 2017 edition of the World Health Organisation Classification of Head and Neck Tumours.